Pehr Strand och speluret på Lövstabruks herrgård - Norrback, Johan (1700-tal: Nordic Journal for Eighteenth-Century Studies, 2021)
Pehr Strand (c. 1758–1826) was the most prominent builder of organ clocks in Sweden around 1800. Strand built in the so-called Berlin tradition, but with clock cases decorated in the typical Gustavian style. The music on the barrels are examples of the typical repertoire performed at different venues in Stockholm, and published in the periodical Musikaliskt Tidsfördrif. A micro-history of the organ clock at the Lövstabruk Manor describes the current position of the research field, and provides, with related sources of different kinds, a reference point for a call to researchers from other fields to contribute in their respectively area of expertise.